Pengaruh Faktor Internal dan Eksternal terhadap Non-Performing Financing Bank Umum Syariah di Indonesia - Selly Yulianti; Tjetjep Djuwarsa; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2022)
The increase in NPF needs serious attention to avoid a fatal impact. The target of this research is to investigate the impact of internal and external determinants on Non Performing Financing at Sharia Commercial Banks in Indonesia during the period of 2015-2019. The sample in this study covers nine Islamic Commercial Banks utilizing quarterly information from 2015-2019. This research used panel data regression analysis with Random Effect Model. The output of this research shows that the Financing to Deposit Ratio, GDP growth, and BI Rate have a positive and significant effect to NPF while the Capital Adequacy Ratio has a negative effect on NPF. Simultaneously, all dependent variables have a significant effect on the NPF.